Reliability analysis of an RC member impacted by a rockfall using a nonlinear SDOF model. (15th April 2015) - Bertrand, D.; Kassem, F.; Delhomme, F.; Limam, A.
Highlights: Failure probability assessment of impacted RC members collapsing under bending. Time effective SDOF model accounting for contact and material non linearities. Fragility curves derivation dedicated to risk analysis involving rockfall hazard. Abstract: This paper presents the reliability analysis of a reinforced concrete (RC) member subjected to an impact arising from a rockfall in order to derive fragility curves dedicated to risk analysis framework. A dynamic model of a simply supported RC member accounting for material and contact nonlinearities has been proposed. In a reliability analysis, several runs of the deterministic model are needed in order to assess the failure probability of the system. Hence ad hoc assumptions are proposed in the aim of reducing the computational cost of the deterministic model, while main physical phenomena involved during the impact are taken into account. Thus Moment–Curvature approach is used and validated with Finite Element Method (FEM) calculations under quasi-static and dynamic loadings. Failure probability is assessed by coupling Monte Carlo, Important Sampling and First Order Reliability Method (FORM) with the simplified deterministic model. Finally, fragility curves are derived which allow underlining the influence of several parameters related either to the loading or the RC member.